Waste Bank Data Management Information System with Web-Based Telegram Bot Notification Feature at Mawar Garbage Bank - Waliyansyah, Rahmat Robi; Novita, Mega (Journal of Intelligent Computing & Health Informatics, 2021)
The Mawar Garbage Bank needs a waste bank data management information system with a Web-based Telegram Bot notification feature on the Garbage Bank. The goal is to provide convenience to the officers of the Mawar Garbage Bank to speed up the process of managing data and delivering information in an effective and efficient manner to customers. This research uses the waterfall method. By using a MySQL database, PHP programming language and Laravel Framework. As well as diagrams used for system modeling using the Unified Modeling Language (UML). With this system, it is hoped that it can make it easier to manage data and provide information about the waste bank which is useful for the Mawar Garbage Bank. This research will be tested using Black Box, White Box and User Acceptance Test (UAT). As for the notification using a telegram bot. The notification from the telegram bot aims to make it easier for customers to find information such as balances, savings flows, and cash withdrawals. From the black box test, you get 100% results, which means that the system has met the design objectives, so this system is suitable for use. White box test results get 100% results with the resulting complexity is 2 which shows that it can meet the criteria for software engineering. The results of the user acceptance test (UAT) test get a 98% result, which means that the software is acceptable and has met the requested needs.